THE EFFECT OF USING POWTOON ON STUDENTS’ READING COMPREHENSION - Perpisa, Lili; Riza, Armilia; Anggara, Sanda (TELL - US JOURNAL, 2023)
The purpose of this research is to find out the effect of using Powtoon on students' reading comprehension. The subjects in this study were VIII grade students of SMPN 40 Padang, which consisted of two classes, namely VIII4, which amounted to 32 students as the experimental group, and VIII2, totaling 32 students as the control group. This is a quantitative study using the quasi-experiment method with a nonequivalent control group design. The experiment group received treatment using Powtoon, while the control group used PowerPoint. The test was utilized to gather data, and one paired sample test was used to analyze it. Meanwhile, the results of the hypothesis test state that H0 is rejected and H1 is accepted based on the sig value.(2-tailed) on the posttest value of the experimental group and the posttest control group with a value of 0.035, which means less than 0.05 The results showed that Powtoon learning media had a significant effect on students' reading comprehension in eight-grade Students at SMPN 40 Padang.